2009
DOI: 10.1038/ajh.2009.103
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Different Indices of Blood Pressure Variability in Hypertensive Patients

Abstract: In this study, high ARV of daytime systolic BP resulted in an independent predictor of cardiovascular risk in hypertensive patients, while high s.d. did not. Our data suggest that, in comparison to s.d., ARV could be a more appropriate index of BP variability and a more useful predictor of outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
212
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(229 citation statements)
references
References 17 publications
6
212
1
4
Order By: Relevance
“…Possible limitations of previous studies were a lack of statistical power, 2-5 selection of specific groups of patients, [5][6][7] categorization of variability by arbitrary cutoff points, 2,4,[7][8][9] and sole reliance on fatal end points. 10,11 Moreover, various parameters can capture short-term blood pressure variability over 24 hours, but most studies only considered the SD of systolic 4,6,12 or diastolic blood pressure or both.…”
mentioning
confidence: 99%
“…Possible limitations of previous studies were a lack of statistical power, 2-5 selection of specific groups of patients, [5][6][7] categorization of variability by arbitrary cutoff points, 2,4,[7][8][9] and sole reliance on fatal end points. 10,11 Moreover, various parameters can capture short-term blood pressure variability over 24 hours, but most studies only considered the SD of systolic 4,6,12 or diastolic blood pressure or both.…”
mentioning
confidence: 99%
“…6 Most studies have found that high 24-hour BP variability is associated with organ damage and may contribute to cardiovascular risk prediction, over and beyond mean BP. [7][8][9][10][11][12][13][14][15][16][17] However, the degree to which variability improves the prediction of cardiovascular risk is controversial. [18][19][20] Previous studies have shown that nighttime BP is generally a better predictor of cardiovascular outcomes than daytime BP in patients with hypertension, and diminished nocturnal decline in BP is associated with or predictive of organ damage and cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…SD has been questioned as an appropriate index of shortterm BPV, considering that SD only reflects the dispersion of values around the mean, does not account for the order in which BP measurements are obtained, and is sensitive to the low sampling frequency of ABPM [16]. In order to improve the prognostic value of short-term BPV, the average real variability (ARV) of daytime and nighttime BP has been introduced as a new index of BPV.…”
Section: Short-term Blood Pressure Variabilitymentioning
confidence: 99%